2016
DOI: 10.2147/ijn.s55807
|View full text |Cite
|
Sign up to set email alerts
|

Fusion between fluid liposomes and intact bacteria: study of driving parameters and in vitro bactericidal efficacy

Abstract: Background Pseudomonas aeruginosa represents a good model of antibiotic resistance. These organisms have an outer membrane with a low level of permeability to drugs that is often combined with multidrug efflux pumps, enzymatic inactivation of the drug, or alteration of its molecular target. The acute and growing problem of antibiotic resistance of bacteria to conventional antibiotics made it imperative to develop new liposome formulations for antibiotics, and investigate the fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Reducing intermembrane hydration repulsion, decreasing bilayer surface density or polarity, and increasing the hydrophobicity of the intermembrane hydrophilic region are known to bring two membranes in close contact (Ohki, 1982;Cevc et al, 1985;Rand and Parsegian, 1989;Burgess et al, 1992;Mondal Roy and Sarker, 2011). Kadurugamuwa suggested that two divalent cations, Mg 2+ and Ca 2+ , which form salt bridges between MVs and the outer membrane, initiate membrane fusion and deliver the autolysin cargo to the cell (Kadurugamuwa and Beveridge, 1996;Wang et al, 2016;Oshima and Sumitomo, 2017). Tashiro and colleagues showed that Buttiauxella agrestis MVs selectively interact with Buttiauxella species.…”
Section: Composition and Action Mechanisms Of Omvsmentioning
confidence: 99%
“…Reducing intermembrane hydration repulsion, decreasing bilayer surface density or polarity, and increasing the hydrophobicity of the intermembrane hydrophilic region are known to bring two membranes in close contact (Ohki, 1982;Cevc et al, 1985;Rand and Parsegian, 1989;Burgess et al, 1992;Mondal Roy and Sarker, 2011). Kadurugamuwa suggested that two divalent cations, Mg 2+ and Ca 2+ , which form salt bridges between MVs and the outer membrane, initiate membrane fusion and deliver the autolysin cargo to the cell (Kadurugamuwa and Beveridge, 1996;Wang et al, 2016;Oshima and Sumitomo, 2017). Tashiro and colleagues showed that Buttiauxella agrestis MVs selectively interact with Buttiauxella species.…”
Section: Composition and Action Mechanisms Of Omvsmentioning
confidence: 99%
“…4,5 Liposomes are vesicles in which an aqueous volume (which can encapsulate hydrophilic compounds) is enclosed by a spherical lipid bilayer (which can encapsulate hydrophobic compounds) typically composed of phospholipids and additional agents like cholesterol. 6 The liposomal lipid bilayer interacts directly with the lipids comprising the cell/bacteria membrane, thus delivering the cargo directly to the cell membrane without having to rely on active or passive uptake of the nanovehicle by target bacterial cells; 7 this makes liposomes specifically advantageous for the localized delivery of high loads of potentially toxic agents that cannot be administered systemically.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is reasonable considering that liposome-liposome or liposome-planner bilayer fusion generally does not frequently occur unless using a chemical or electrical stimulus 54 , 55 . Several studies showed that in the absence of fusion enhancing reagents or stimulus, the liposome-liposome fusion does not occur or even at the best cases several times per 100 μm 2 56 60 . The fusion rate of protoplast into ALBiC bilayer corresponds to 1.5~2.3 × 10 −2 times per 100 μm 2 within the reported values.…”
Section: Discussionmentioning
confidence: 99%